Fenomen masowej mobilizacji lokalnej. Przypadek budżetu obywatelskiego w gminie Sława = The phenomenon of mass mobilization in local communities. The civic budget of Sława municipality case - Hermaszewski, Jarosław; Kwiatkowski, Mariusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article is a case study. The subject of analysis is mass participation of the inhabitants of one of the municipalities in the vote on participatory budgeting. The turnout of 70% was considered to be a phenomenon that requires explanation. The article describes the process of preparation and conduct of the voting. Several factors of mass mobilization were identified: (1) long-term policy of the municipal authorities, of engaging citizens in decision-making processes relating to the management of the budget (development fund, local fund), (2) recognition of the designs to be attractive by inhabitants from the point of view of fulfilling their common needs (recreational facilities, areas of integration), (3) a simultaneous mobilization of both levels - grassroots (spontaneous groups of citizens) and top-down (local authorities decisions).
Keywords: budżet obywatelski; mobilizacja lokalna; partycypacja; kapitał społeczny; participatory budget; local mobilization; participations; social capital